2014
DOI: 10.1093/mnras/stu2299
|View full text |Cite
|
Sign up to set email alerts
|

Carbon abundance and the N/C ratio in atmospheres of A-, F- and G-type supergiants and bright giants

Abstract: Based on our prior accurate determination of fundamental parameters for 36 Galactic A-, F-and G-type supergiants and bright giants (luminosity classes I and II), we undertook a non-LTE analysis of the carbon abundance in their atmospheres. It is shown that the non-LTE corrections to the C abundances derived from C I lines are negative and increase with the effective temperature T eff ; the corrections are especially significant for the infrared C I lines with wavelengths 9060-9660Å. The carbon underabundance a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…For example all enhancements are less than those predicted for v o ≈ 400 km s −1 . Other recent studies such as those by Lyubimkov et al (2015) of A-, F-, and G-type supergiants in our Galaxy, have also shown good agreement with rotational stellar models with initial rotational velocities of 0−300 km s −1 .…”
Section: Nitrogen Abundances and Atmospheric Parameterssupporting
confidence: 86%
See 1 more Smart Citation
“…For example all enhancements are less than those predicted for v o ≈ 400 km s −1 . Other recent studies such as those by Lyubimkov et al (2015) of A-, F-, and G-type supergiants in our Galaxy, have also shown good agreement with rotational stellar models with initial rotational velocities of 0−300 km s −1 .…”
Section: Nitrogen Abundances and Atmospheric Parameterssupporting
confidence: 86%
“…For example, an analysis of A-, F-, and G-type Galactic supergiants by Lyubimkov et al (2015) found both an underabundance of carbon together with an anticorrelation between the carbon and nitrogen abundances. These were consistent with mixing between the stellar core and surface during either a main sequence (MS) and/or the first dredge-up phase.…”
Section: Element Abundancesmentioning
confidence: 99%
“…Hayek et al (2011) updated the Collet et al (2007) Thus, the discrepancy between the C I and CH-based abundances found by Tomkin et al (1992) in the classical 1D analysis is expected to be larger in 3D. The NLTE methods for C I were developed by Vernazza et al (1981), Shchukina & Shcherbina (1990), Stuerenburg & Holweger (1990), Takeda (1992), Przybilla et al (2001), Fabbian et al (2006), and Lyubimkov et al (2015). Stuerenburg & Holweger (1990) showed that NLTE removes a discrepancy between visible and near-IR lines of C I in the Sun, while the difference in LTE abundances between individual lines can be up to 0.37 dex, for example between C I 9111Å and 5380Å.…”
Section: Introductionmentioning
confidence: 99%
“…The Lyubimkov et al (2015) studied the NLTE effects for C I in the galactic A-, F-and G-type supergiants and bright giants.…”
Section: Introductionmentioning
confidence: 99%
“…Is there such accordance in the case of AFG supergiants and bright giants? In order to answer this question, it would be useful to remember the above-mentioned N vs C anticorrelation in these stars obtained by Lyubimkov et al (2015) (see Fig.12 there). Like the present paper, a comparison between the observed and computed relations has been implemented there for the same two phases: post-MS and post-FDU.…”
Section: Discussionmentioning
confidence: 99%